Foreign experience of realization of the personied approach to development of management personnel of educational organization - V. V. Tarasenko (Управление)
The results of a study of foreign practices in the development of management personnel of educational organizations in Australia, Denmark, Finland, France and the United States of America for the presence of markers of a personalized approach are presented. The features of the implementation of a personalized approach to the development of management personnel of foreign educational organizations are revealed and described: the recognition and strict observance of the rights and freedoms, abilities and capabilities of management personnel as a subject of development; the focus of the development system on internal motivation, transformation of common values (education system, the state and society as a whole) in the personal values of management personnel; the continuity of the personnel development system with a focus on the emerging socio-professional experience of the subject of development. The recommendations for the design of the domestic personalized system of development of management personnel of educational organization are developed. The risks identified by the analysis of foreign personalized systems of development of management personnel of educational organizations, which are recommended to take into account in the design and implementation of the relevant domestic system, - are presented: the lack of a systematic approach to the professional development of the head; low integration of the goals and strategies of professional development of the head with the goals and strategy of the educational organization / education system; insufficient orientation of training programs on personalized opportunities, including the accumulated professional and social experience of the subject of development; the lack of a specially trained body of Tutors (mentors, mentors, coaches) in the field of personalized support of the management personnel of the educational organization; a limited number of objective, scientifically based criteria and indicators for assessing the effectiveness of a personified system of personnel development and, as a consequence, the inability to conduct objective monitoring and reflection of the results of the development of management personnel.